TV Advertising in MBC channel An analytical study of the most prominent of the advertisements presented in Ramadan 2018 (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Advertisements attract various media outlets because of the added revenue to media and MBC channels are considered one of the most watched channels.The study aimed to• Identify the form of MBC channel ads• Identify the content of MBC channel ads byThe community research consisted of all the ads in MBC1 but only 61 ads were chosen from them and all TV-series ,programs ads and break ads were excludedThe study reached a number of results, the most important of which are• Food and beverage items ranked high among (commodity ads)• The value of  developing  a sense for beauty was   higher than the other values• The most important temptations used are entertainment and  followed by the temptations of the need for food and drink.